Anterolateral distal tibia locking plate osteosynthesis and their ability to capture OTAC3 pilon fragments. Issue 2 (February 2018) - Aneja, Arun; Luo, T. David; Liu, Boshen; Domingo, Molina; Danelson, Kerry; Halvorson, Jason J.; Carroll, Eben A.
Abstract: Background: Intra-articular Pilon fractures remain therapeutically challenging due to osteochondral fracturing and comminution, marginal impaction, and insult to the soft tissue envelope. The purpose of this study was to compare the efficacy of anterolateral distal tibial locking plates in capturing main fracture fragments in tibial plafond fractures. Methods: From May 2011 to Dec 2015, 169 OTA C-type pilon fractures met inclusion and exclusion criteria with computed tomographic (CT) scans performed prior to definitive fixation. For each patient, the fracture lines were mapped, digitized, and graphically superimposed to create a compilation of fracture lines. Based on these average measurements, three distal tibia sawbones had three different anterolateral plates applied. Axial CT scan images were used to determine the efficacy of screw purchase in main fracture fragments in pilon fractures. Results: The Smith & Nephew PERI-LOC plate secured the largest number of fracture lines (90.1%) but missed the Volkmann fragment with greatest frequency at 3.6%. The Synthes 2.7/3.5 mm VA-LCP captured 87.3% of the fracture lines while missing the Volkmann fragment 3.2% of the time. The Synthes 3.5 mm LCP captured 86.5% of the fracture lines but was the best at securing the Volkmann fragment (1.2% missed). All three implants were deficient in capturing the medial malleolar fragment. The PERI-LOC and 2.7/3.5 mm VA-LCP did not differ with respect to percentage of fragments captured (p = 0.721) but both outperformed the 3.5 mm LCP (p = 0.021 and p = 0.05, respectively). Conclusions: This study was consistent with prior literature in defining three main fracture fragments: anterior, medial, and posterior. All three plates were deficient in capturing the medial malleolar fragment. The Smith and Nephew PERI-LOC plate secured the most number of fracture lines, while the Synthes 3.5 mm LCP was least likely to miss the Volkmann fragment and most likely to miss the medial malleolar fragment. No plate was found to be superior to the other in capturing all fracture lines of the OTAC3 pilon fragments. Level of evidence: Three.